Retrospective Evaluation of the Frequency of Acute Pancreatitis in Adult Hospitalized Patients with COVID-19 Infection - Dilşah BAŞKOL ELİK; Nevin ORUÇ; Ezgi GÜLER; Hüseyin Aytaç ERDEM; Funda KARBEK AKARCA; Oğuz Reşat SİPAHİ; Ahmet Ömer ÖZÜTEMİZ; Hüsnü PULLUKÇU; Meltem TAŞBAKAN; Candan ÇİÇEK; Tansu YAMAZHAN (Mediterranean Journal of Infection, Microbes and Antimicrobials, 2022)
Introduction: Data on the relationship between Coronavirus disease-2019 (COVID-19) and acute pancreatitis are limited. This study aimed to investigate the possible role of COVID-19 in the etiology of acute pancreatitis in a tertiary-care educational university hospital by retrospectively evaluating the incidence of acute pancreatitis in adult hospitalized patients with COVID-19. Materials and Methods: Severe acute respiratory syndrome-Coronavirus-2 (SARS-CoV-2) polymerase chain reaction (PCR)-positive adult inpatients from March 15, 2020, to February 1, 2021, constituted the study group in our hospital. This cohort was analyzed for acute pancreatitis criteria, including acute abdominal pain, increased amylase and/or lipase more than three times the normal value, and radiological finding supporting the disease. Patients who met at least two of the acute pancreatitis diagnostic criteria were determined, and those who met the criteria during or after SARS-CoV-2 PCR positivity detection were included in the study. These patients were further analyzed for COVID-19-related data and pancreatitis severity status. Results: Our hospital had 1227 inpatients with COVID-19 diagnosis in one year. A total of four cases met the inclusion criteria. Acute pancreatitis rates were detected at 0.3% and 1.07% for all cohorts (n=1227) and the pancreatic enzyme-tested group (n=372), respectively. Of these four patients, two (50%) were females (50%) and the mean age was 70.7 (range: 64-79) years. There was no correlation between COVID-19 pneumonia and pancreatitis severity scores, including Ranson, Acute Physiologic Assessment and Chronic Health Evaluation 2, and modified computed tomography severity scores. Conclusion: COVID-19 is a rare risk factor for acute pancreatitis and did not affect the pancreatitis severity or mortality in our cohort.